Perforated composite plate girders with intermediate inclined stiffeners subjected to combined shear and bending - Mohd Eizlan Majuk,; Mohd Reza Azmi,; Mohd Yazmil Md Yatim,; Kabir Ahmad, Irfana; Mukhlisin, M. (Penerbit Universiti Kebangsaan Malaysia, 2022)
This paper discusses the ultimate strength of composite plate girders with intermediate inclined stiffeners. The inclination angle of intermediate stiffener, web opening size and span length are the key factors influencing the performance of the composite plate girder. This study used the LUSAS software to develop 20 non-linear finite element models using intermediate stiffener different inclination angles, web opening sizes and span lengths. The intermediate stiffener have an inclination angle of 90°, 75°, 60°, 45° and 30°. The web plates were divided into six or eight sub-panel webs depending on the span length using the intermediate inclined stiffener. The ultimate strength and behaviour of the composite plates are influenced by the inclination angle of the intermediate stiffener, web opening size and span length. Generally, the ultimate strength of the composite plate girder increased when the inclination angle was reduced from 90° to 30° with a corresponding reduction in the web opening size and span length. The increase in the ultimate strength are 44.63% for the web plate with do = 100 mm and L = 3450 mm, 20.41% for the web plate with do = 200 mm and L = 4500 mm, 216.41% for the web plate with do = 100 mm and L = 3450 mm, and 58.89% for the web plate with do = 200 mm and L = 4500 mm due to the formation of tension field on the web panels. The width of the tension field in the plastic hinge increased and shifted depending on the top and bottom flange when using the intermediate inclined stiffener. The composite plate girder with a small web opening of do = 100 mm exhibited a high ultimate strength. The ultimate strength of the composite plate girder with a 60° inclined intermediate stiffener is higher than the intermediate stiffener with a 75° inclination angle. Therefore, the composite plate girder with an inclined intermediate stiffener has a higher ultimate strength.